The importance of urban green spaces in the development of smart cities - Addas, Abdullah (Frontiers in Environmental Science, 2023)
In the era of modernization, urban green spaces (UGSs) are attracting increasing attention in smart city (SC) development. There is a paucity of UGSs, and their importance has become crucial in enhancing life expectancy and health. To meet people's demands, scientists are busy designing smart cities under flagship programs for urban transformation. UGSs are relevant in the analysis and investigation of improved lifestyles. The scarcity of UGSs can have many social and physical impacts. The presence of UGSs in smart cities is proposed to improve residents' lifestyles. Semi-structured interviews were conducted with residents, officials and government experts to inform the development of UGSs further. The result of the surveys analyzed using the MAXQDA software, which presents the importance of SC and the residents' satisfaction. The results show an urgent requirement for larger UGSs to enhance urban environments' security and economic opportunities. The deployment of USGs is particularly relevant to fully enhancing residents' lifestyles and health. The present research aligned with the World Health Organization (WHO) standards to identify the scope of UGS initiatives in different parts of the city of Graz, Austria, and recommendations for improving the quality of future UGS planning is provided. The proposed research results conclude that UGS is a valid alternative to enhance air quality, with measurable and substantial air pollution changes even in space-constrained sites.